Ferroptosis and gut microbiota: A new horizon in alcohol-associated liver disease management - Yue Chen; Wenkang Gao; Kailin Cai; Ling Yang; Huikuan Chu (Cellular and Molecular Life Sciences)
Abstract Alcohol-associated liver disease (ALD) is one of the most common chronic liver diseases worldwide, contributing significantly to liver cirrhosis and hepatocellular carcinoma, with limited effective treatment options. Approximately 50% of patients with ALD exhibit iron overload, which can further trigger the occurrence of ferroptosis. Recent studies indicate that ferroptosis plays a role in the development and progression of ALD through pro-inflammatory and pro-fibrotic mechanisms. Additionally, the gut microbiota exerts a complex influence on ALD, with pathogens like Candida albicans and Enterococcus faecalis promoting its progression, whereas Bifidobacterium appears to have a protective effect. Emerging findings indicate that microorganisms like Lactobacillus and metabolites such as 1,3-diaminopropane and reuterin can modulate iron homeostasis. However, the intrinsic link between gut microbiota–derived metabolites and ferroptosis in ALD remains inconclusive. This review comprehensively synthesizes current knowledge regarding the microbiota–ferroptosis crosstalk in ALD, with particular emphasis on microbial regulation of hepatic iron homeostasis and microbiota-driven modulation of oxidative stress through lipid peroxidation and antioxidant system interactions. Notably, we propose either suppressing hepatic ferroptosis or inducing ferroptosis in pathogenic bacterial strains as dual therapeutic strategies to mitigate ALD progression. These insights highlight the therapeutic potential of the gut microbiota-ferroptosis axis, paving the way for precision management strategies in ALD. Graphical Abstract Gut microbiota-liver ferroptosis crosstalk in alcohol-associated liver disease (ALD). Alcohol consumption disrupts gut microbiota homeostasis, characterized by a reduction in beneficial bacteria and an increase in harmful bacteria, and enhances intestinal iron absorption. The resulting dysbiosis can further exacerbate iron uptake. Together, elevated iron levels and dysbiosis-induced oxidative stress and lipid peroxidation contribute to the induction of ferroptosis, thereby accelerating the progression of ALD. Targeting the gut microbiota–liver ferroptosis axis thus represents a promising therapeutic strategy for ALD. Abbreviations: FMT, fecal microbiota transplantation.